2000
DOI: 10.1901/jeab.2000.74-55
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discrimination Under Two Concurrent Fixed‐interval Fixed‐interval Schedules

Abstract: Pigeons were trained to discriminate 5.0 mg/kg pentobarbital from saline under a two-key concurrent fixed-interval (FI) 100-s FI 200-s schedule of food presentation, and later tinder a concurrent FI 40-s FI 80-s schedule, in which the FI component with the shorter time requirement reinforced responding on one key after drug administration (pentobarbital-biased key) and on the other key after saline administration (saline-biased key). After responding stabilized under the concurrent FI 100-s FI 200-s schedule, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Pigeons P360, P347, and P380 had been trained in previous drug-discrimination experiments to discriminate between pentobarbital and saline (McMillan, Hardwick, & Li, 2001;McMillan & Li, 2000). These pigeons were further trained to discriminate among pentobarbital, amphetamine, a combination of these drugs, and saline (the amphetaminepentobarbital group).…”
Section: Methodsmentioning
confidence: 99%
“…Pigeons P360, P347, and P380 had been trained in previous drug-discrimination experiments to discriminate between pentobarbital and saline (McMillan, Hardwick, & Li, 2001;McMillan & Li, 2000). These pigeons were further trained to discriminate among pentobarbital, amphetamine, a combination of these drugs, and saline (the amphetaminepentobarbital group).…”
Section: Methodsmentioning
confidence: 99%
“…We have also demonstrated that rats can be trained in the peak-interval procedure to use interoceptive cues to predict the time of reinforcement. Using a drug-discrimination approach, in which the administration, and subsequent interoceptive effects, of a pharmacological agent serve as the discriminative stimulus for operant responding ( Kubena and Barry, 1969 ; Krimmer et al, 1984 ; McMillan and Hardwick, 2000 ; McMillan and Li, 2000 ), Kurti et al (2014) trained rats that when saline was administered before the experimental session, a tone cue signaled that reinforcement was probabilistically available after 5 s. However, if a low dose of amphetamine (0.5 mg/kg) was administered prior to the experimental session, the same tone cue signaled that reinforcement was probabilistically available after 20 s. An examination of data from the first five trials of each session (before feedback) demonstrated that the rats could accurately use their interoceptive state to predict the time of reinforcement, as they peaked at 5 s following saline injections, but they peaked at 20 s after receiving amphetamine. Similar results were obtained when rats were given saline or amphetamine injections immediately before final test sessions composed entirely of probe trials.…”
Section: Introductionmentioning
confidence: 99%